Addition
 
10 + 9 = 6 + 11 = 8 + 6 = 10 + 12 =
8 + 8 = 5 + 1 = 8 + 1 = 4 + 7 =
3 + 7 = 3 + 4 = 11 + 8 = 7 + 6 =
10 + 10 = 2 + 8 = 1 + 2 = 1 + 4 =
5 + 9 = 1 + 2 = 4 + 6 = 5 + 12 =
3 + 8 = 0 + 5 = 4 + 1 = 9 + 11 =
11 + 11 = 12 + 8 = 7 + 8 = 3 + 6 =
6 + 10 = 11 + 12 = 10 + 3 = 7 + 5 =
10 + 6 = 6 + 11 = 5 + 7 = 10 + 0 =
5 + 8 = 5 + 2 = 8 + 1 = 1 + 8 =
3 + 7 = 4 + 5 = 11 + 5 = 8 + 6 =
11 + 10 = 3 + 8 = 1 + 12 = 11 + 1 =
6 + 9 = 2 + 12 = 1 + 7 = 6 + 0 =
0 + 9 = 1 + 2 = 4 + 1 = 9 + 11 =
12 + 11 = 12 + 5 = 7 + 9 = 3 + 7 =
6 + 10 = 11 + 12 = 10 + 3 = 7 + 5 =
1 + 10 = 10 + 2 = 10 + 11 = 1 + 0 =
9 + 12 = 6 + 6 = 0 + 2 = 5 + 12 =
4 + 12 = 5 + 9 = 3 + 9 = 12 + 10 =
2 + 11 = 3 + 12 = 2 + 4 = 3 + 5 =
10 + 0 = 2 + 3 = 5 + 11 = 10 + 4 =
5 + 0 = 1 + 6 = 8 + 5 = 0 + 12 =
12 + 12 = 0 + 9 = 11 + 0 = 4 + 11 =
11 + 2 = 12 + 0 = 11 + 4 = 11 + 6 =
5 + 1 = 11 + 3 = 1 + 11 = 2 + 4 =